1987
DOI: 10.3758/bf03205020
|View full text |Cite
|
Sign up to set email alerts
|

The effects of activity conditioned in random CS/US training on performance in autoshaping

Abstract: Random presentations of key lights and food retarded acquisition and suppressed asymptotic rates of keypecking in autoshaping. Sequences of 10 sessions of random training alternated with 10 sessions of autoshaping resulted in poor performance (in terms of both the acquisition and asymptotic indices) relative to a group that received sequences of CS-only (rather than random) training alternating with autoshaping. When the birds that previously were trained with the random sequence were exposed to CS-alone extin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Besides providing information about behavior during the CS, the present study also provides information about behavior during the ITI and about the differential control exerted by the CS and the ITS. Behavior during the ITI was stereotyped, as has been found in other studies (e.g., Brandon & Paul, 1987;Eldridge & Pear, 1987;Matthews & Lerer, 1987;Pear & Eldridge, 1984), and the pattern of the stereotyped behavior did not depend in any obvious way on the position of the CS and the ITS or on whether sign-tracking or goal-tracking occurred. It should be noted that although in this study the movement patterns during the ITI tended to occur along the wall on which the food aperture was located, this is not always the case (Eldridge & Pear, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…Besides providing information about behavior during the CS, the present study also provides information about behavior during the ITI and about the differential control exerted by the CS and the ITS. Behavior during the ITI was stereotyped, as has been found in other studies (e.g., Brandon & Paul, 1987;Eldridge & Pear, 1987;Matthews & Lerer, 1987;Pear & Eldridge, 1984), and the pattern of the stereotyped behavior did not depend in any obvious way on the position of the CS and the ITS or on whether sign-tracking or goal-tracking occurred. It should be noted that although in this study the movement patterns during the ITI tended to occur along the wall on which the food aperture was located, this is not always the case (Eldridge & Pear, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, autoshaped keypecking by pigeons might not be a good preparation for testing the predictions of the comparator hypothesis concerning modification of the associative status of the comparator stimuli after completion of CS training. Consistent with this conclusion, Locurto, Travers, Terrace, and Gibbon (1980) found that unsignaled US presentations to pigeons in a context subsequently used for autoshaping resulted in elevated activity levels (also see Brandon & Paul, 1987). The elevated activity levels apparently distracted the animals from the keylight CSs, thereby impeding acquisition of the keylight—US association.…”
Section: Critique Of Robbins's Experimentsmentioning
confidence: 64%
“…The results of testing suggest that if this was the case, those responses interfered not only with performance to the target, but also with learning about the target; removing the signal from the target during testing failed to have a dramatic effect on responding to the target. Competing responses elicited by the signal may have interfered with learning about the target by removing the pigeons from the key and thus reducing the pigeons' exposure to the target-food relation (cf., Brandon & Paul, 1987). On the other hand, the blocking effect might be due not to peripheral response competition but rather to associative interference at a more central level of processing (e.g., Mackintosh, 1975; Rescorla & Wagner, 1972; Wagner, 1981).…”
Section: Resultsmentioning
confidence: 99%